2007
DOI: 10.1007/s00417-007-0721-3
|View full text |Cite
|
Sign up to set email alerts
|

Pulfrich’s phenomenon in optic nerve hypoplasia

Abstract: A case of mild ONH with normal visual function in each eye resulted in a small inter-ocular delay associated with errors in visual perception consistent with a spontaneous Pulfrich effect. Wearing a pair of glasses with the right lens tinted eliminated these difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…On top of a reduction in retinal illumination, it has been suggested that a unilateral cataract can also cause a spontaneous Pulfrich effect through retinal defocusing, i.e., blurring, which also slows retinocortical transmission and increases visual latency [23]. However, Cetinkaya et al [23,24] Corneal opacity [21] Iatrogenic, e.g., uniocular mydriasis, X-chrom lens [19] Traumatic anisocoria [21] Affecting neural conduction Post retinal detachment repair [21] Macular disease [26,27] Asymmetric pigmentary glaucoma [22] Central pathway conditions Optic neuritis/multiple sclerosis [21,[33][34][35][36][48][49][50] Mid-facial injuries [31,32] Other optic nerve pathologies [28][29][30]51] Pituitary tumours and temporoparietal astrocytomas [38] Anisometropic amblyopia [16] reported that the magnitude of the spontaneous Pulfrich effect in patients with unilateral cataracts did not correlate with visual acuity, but correlated with the presence of binocular symptoms [25]. Indeed, it has been suggested that the presence of the Pulfrich effect may account for visual symptoms in patients with unilateral cataracts that are independent of visual acuity, stereoacuity and contrast sensitivity [23].…”
Section: The Spontaneous Pulfrich Effect In Certain Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On top of a reduction in retinal illumination, it has been suggested that a unilateral cataract can also cause a spontaneous Pulfrich effect through retinal defocusing, i.e., blurring, which also slows retinocortical transmission and increases visual latency [23]. However, Cetinkaya et al [23,24] Corneal opacity [21] Iatrogenic, e.g., uniocular mydriasis, X-chrom lens [19] Traumatic anisocoria [21] Affecting neural conduction Post retinal detachment repair [21] Macular disease [26,27] Asymmetric pigmentary glaucoma [22] Central pathway conditions Optic neuritis/multiple sclerosis [21,[33][34][35][36][48][49][50] Mid-facial injuries [31,32] Other optic nerve pathologies [28][29][30]51] Pituitary tumours and temporoparietal astrocytomas [38] Anisometropic amblyopia [16] reported that the magnitude of the spontaneous Pulfrich effect in patients with unilateral cataracts did not correlate with visual acuity, but correlated with the presence of binocular symptoms [25]. Indeed, it has been suggested that the presence of the Pulfrich effect may account for visual symptoms in patients with unilateral cataracts that are independent of visual acuity, stereoacuity and contrast sensitivity [23].…”
Section: The Spontaneous Pulfrich Effect In Certain Pathologiesmentioning
confidence: 99%
“…Disorders affecting the retina, including central serous elevation of the macula [26], unilateral epiretinal membrane of the macula [27] and repaired retinal detachment [21], can delay conduction and have been reported to manifest a spontaneous Pulfrich effect associated with increased visual latency. Neural conduction can also be slowed in asymmetric optic nerve pathologies such as optic nerve hypoplasia [28], optic nerve head drusen [29], acute ischaemic optic neuropathy due to a presumed vascular accident [30], traumatic optic neuropathy due to mid-facial injury [31,32], and optic neuritis commonly associated with multiple sclerosis [21,[33][34][35][36].In patients with optic neuritis, the Pulfrich effect may account for difficulties with motion perception even in apparent recovery from optic neuritis, as it can be present due to residual optic nerve defects, and appears not to be related to the extent of acute visual loss and time elapsed since an attack of acute optic neuritis [34]. Interestingly, an asymptomatic inter-ocular signal latency difference in patients with multiple sclerosis can manifest as a spontaneous Pulfrich effect after exercise, presumably due to increased body temperature causing the Uthoff effect [37].…”
Section: The Spontaneous Pulfrich Effect In Certain Pathologiesmentioning
confidence: 99%